1989
DOI: 10.4315/0362-028x-52.9.642
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Salmonella, Campylobacter, and Yersinia enterocolitica in Swine Carcasses and the Slaughterhouse Environment

Abstract: This study was done to evaluate the degree of contamination of cooler-ready hog carcasses and the slaughterhouse environment by Salmonella spp., Campylobacter spp. and Yersinia enterocolitica. Samples from diaphragms and feces were collected from 200 market hogs in a Quebec slaughterhouse. Scalding-tank water and environmental swabs were also collected in the slaughterhouse. Specimens were tested for the presence of Salmonella spp., Y. enterocolitica, and Campylobacter spp. Salmonella spp. were isolated from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

1998
1998
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 0 publications
1
15
0
3
Order By: Relevance
“…This fact has also been reported by Mafu et al [4] and Pearce et al [44]. The latter researchers have also reported that Salmonella was found in 31 % of carcasses, after bleeding.…”
Section: Microorganisms Indicating Faecal Contaminationsupporting
confidence: 79%
See 1 more Smart Citation
“…This fact has also been reported by Mafu et al [4] and Pearce et al [44]. The latter researchers have also reported that Salmonella was found in 31 % of carcasses, after bleeding.…”
Section: Microorganisms Indicating Faecal Contaminationsupporting
confidence: 79%
“…Swine and poultry are the most common Salmonella reservoirs among different animal species [3][4][5][6][7][8][9][10][11][12], and it has been shown that only a few colonyforming units (c.f.u.) are necessary for infection in predisposed subjects [7].…”
Section: Introductionmentioning
confidence: 99%
“…This figure is in keeping with the prevalence of Salmonella sp. contamination of pork carcass surfaces reported by other authors, ranging from 10 to 20% (17,27,37), especially since our use of composite rather than individual samples probably leads to somewhat overestimating the proportion of contaminated half carcasses. In 1994, Denys (personal communication) obtained a contamination rate of 4.6% on swabs from pork carcasses and 6.4% in minced meat made from pork pieces.…”
Section: Anderson Et Al (1)mentioning
confidence: 78%
“…Most of the Y. enterocolitica isolates recovered from environmental samples, including the slaughterhouse, fodder, soil, and water, have been nonpathogenic (8,22,24,97,125,140 (Table 5).…”
Section: Environmental Samplesmentioning
confidence: 99%